Onboarding Strategis: Kunci Keberhasilan Kinerja dan Retensi Pegawai (Studi Kasus di Yayasan Ukhuwah Kalimantan Selatan) - Halimatussa'diyah, Halimatus; Rezani, Muhammad Rizki (Jurnal Penelitian Pendidikan, 2025)
This study aims to examine the Onboarding process as a key element in enhancing employee performance and retention at the Ukhuwah Foundation in South Kalimantan. Effective Onboarding is intended to help new employees perform their tasks well and adapt to the work environment, thereby improving productivity, engagement, and employee loyalty. By implementing a systematic Onboarding process, organizations can prevent failures during the transition period and ensure new employees feel integrated. This study employs a qualitative approach using in-depth interviews, observations, and documentation to collect relevant data. Data analysis is conducted using the interactive model by Miles and Huberman, which includes the stages of data collection, reduction, display, and conclusion drawing to ensure the accuracy of results. The findings of the study indicate that the Onboarding strategies implemented at the Ukhuwah Foundation significantly support the adaptation of new employees, strengthen their understanding of the organizational work culture, and enhance task efficiency and job satisfaction. Therefore, structured Onboarding becomes an essential instrument in creating a conducive and productive work environment.